Application of Lean Thinking in Reducing Turn Around Time on the Quality Control Process at Nickel Processing Plant - Sagita, Pendra; Singgih, Moses Laksono (IPTEK Journal of Proceedings Series, 2020)
This work presents a case study focused on reducing the turn around time in the quality control process at Nickel processing plant, using Lean Thinking tools. The Nickel industry, the process is drying, reducting, smelting, and converting. This process needs to be controlled to get the optimal result, and the process needs to be controlled quickly. So the analysis data must be generated in a short time. They are recording time and activities from sampling until reporting the data carried out to analyze the current situation using value stream mapping to identify the main problem, such as high waiting times. The root cause of the main problem is sought by using the fishbone diagram and given an improvement suggestion according to the origins of the problem. The application of these improvements can reduce the analysis time in the quality control process by 98.52% of the total cycle time.